The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmolb.2021.646574
|View full text |Cite
|
Sign up to set email alerts
|

A GC-MS/Single-Cell Method to Evaluate Membrane Transporter Substrate Specificity and Signaling

Abstract: Amino acid transporters play a vital role in metabolism and nutrient signaling pathways. Typically, transport activity is investigated using single substrates and competing amounts of other amino acids. We used GC-MS and LC-MS for metabolic screening of Xenopus laevis oocytes expressing various human amino acid transporters incubated in complex media to establish their comprehensive substrate profiles. For most transporters, amino acid selectivity matched reported substrate profiles. However, we could not dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 117 publications
2
26
0
Order By: Relevance
“…These data suggested that TgApiAT6-1 may be a Lys transporter, although it could also mediate the uptake of other amino acids not detected under the transport conditions of the experiments, or not detected by GC-MS, such as Arg. Arg is readily converted into L-ornithine during sample preparation for GC-MS such that very little remains chemically unmodified [34,35].…”
Section: Tgapiat6-1 Is a High Affinity Lysine Transportermentioning
confidence: 99%
See 3 more Smart Citations
“…These data suggested that TgApiAT6-1 may be a Lys transporter, although it could also mediate the uptake of other amino acids not detected under the transport conditions of the experiments, or not detected by GC-MS, such as Arg. Arg is readily converted into L-ornithine during sample preparation for GC-MS such that very little remains chemically unmodified [34,35].…”
Section: Tgapiat6-1 Is a High Affinity Lysine Transportermentioning
confidence: 99%
“…To measure whether AA + accumulation occurs in TgApiAT6-1 and TgApiAT1-expressing oocytes, we used a targeted LC-MS/MS approach to measure intra-oocyte substrate concentrations while accounting for the endogenous metabolism of these substrates [35].…”
Section: Tgapiat1mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in this work, the presence of substrates normally not present in the cytoplasmatic environment, allowed us to develop an alternative method for investigating the actual translocation of the substrate inside the cell, we evaluated the amount of D-amino acids in the single oocyte by analyzing the cytoplasmic content by HPLC [ 120 ]. This method has only recently been implemented by the use of GS-MS allowing to measure in a determined and precise way the basal content of metabolite in oocytes and, in oocytes expressing different membrane transporters, the amount of transported substrate in a single cell after exposure to different medium [ 145 ]. Finally, it is important to underline how the transport of D-amino acids by the insect NATs could be of particular interest, given the recent approach that involves the use of insects for the treatment of organic waste for the production of molecules of nutraceutical, pharmacological and nutritional interest [ 146 , 147 ].…”
Section: From Kaat1 ( Manduca Sexta Amino Acid Transporter) To Gaba Transporter Structure–functionmentioning
confidence: 99%